The impact of leisure time physical activity on mental health and health perception among people with cancer - Jaehyun Kim; Junhyoung Kim; Areum Han (Tabriz University of Medical Sciences, 2020)
Background: People with cancer often report high levels of negative psychological symptoms and poor perception of health due to cancer treatment and activity limitations. Prior studies have suggested that participation in leisure time physical activity (LTPA) can reduce negative psychological symptoms and improve health perception. However, a few studies have examined the contribution of LTPA to health benefits among people with cancer. Thus, we aimed to examine how a different level of LTPA engagement contributed to mental health and health perceptions among people with cancer. Methods: Using the 2017 Health Information National Trends Survey (HINTS) data, cross sectional data of 504 respondents diagnosed with any types of 22 cancers listed in the survey questionnaire were analyzed. A multivariate analysis of variance (MANOVA) was used to test for mean differences in mental health and health perception among the three different LTPA groups(i.e., inactive, moderately active, and vigorously active groups). Results: Results indicated that people with cancer who reported higher levels of LTPA scored higher on mental health and health perception than those with lower levels of LTPA (Pillai's trace= 0.060, F (4,944) = 15.06, P < 0.001). Conclusion: This finding suggests that individuals with cancer gained more health benefits through high engagement in LTPA. Moreover, we suggested that LTPA can be used as an important therapeutic intervention to promote health quality and wellbeing among people with cancer. Implications for practical suggestions are further discussed.